Clonal architecture in patients with myelodysplastic syndromes and double or minor complex abnormalities: Detailed analysis of clonal composition, involved abnormalities, and prognostic significance. Issue 11 (24th September 2018) - Schanz, Julie; Solé, Francesc; Mallo, Mar; Luño, Elisa; Cervera, Jose; Granada, Isabel; Hildebrandt, Barbara; Slovak, Marylin L.; Ohyashiki, Kazuma; Fonatsch, Christa; Pfeilstöcker, Michael; Nösslinger, Thomas; et al.
Abstract: The study analyzes the clonal architecture and the abnormalities involved in a series of 191 patients with myelodysplastic syndromes (MDS) and 2‐3 clonal abnormalities. All patients were extracted from an international database. The patients were classified into six clonal subtypes (2A‐3C) based on the number of abnormalities and the presentation of unrelated clones (UC) and/or a clonal evolution. UC were detected in 23/191 patients (12%). The composition of UC showed great variability. The only recurrent combination of abnormalities was del(5q) and + 8 in 8 of 23 patients (35%). In patients with clonal evolution, the clone size of the primary and secondary clone varied: Patients with −7 and + 8 in the primary clone showed a larger primary and a smaller secondary clone (−7: median 74% vs 10%; +8 73% vs 18%) while patients with del(5q) in the primary clone showed a smaller primary and a larger secondary clone (33% vs 61%). Univariate and multivariate analyses showed no significant differences regarding overall or AML‐free survival between the clonal subtypes. Only the subtype 3C (3 abnormalities and clonal evolution) was an independent risk factor for developing AML (Hazard Ratio 5.5 as compared to subtype 2A, P  < .05). Finally, our study confirms that the number of abnormalities clearly defines a significant risk factor for overall‐ as well as AML‐free survival. Importantly, in patients with more than one clone, the calculation of the number of abnormalities in the entire sample instead of the number of abnormalities per clone allows a higher prognostic accuracy.